Electrical Behaviors of Flame Retardant Huntite and Hydromagnesite Reinforced Polymer Composites. (15th October 2012) - Yılmaz Atay, Hüsnügül; Çelik, Erdal
Abstract : In our previous work, we studied the physical characteristics (particle size, surface treatment, etc.) of huntite/hydromagnesite mineral in order to be employed as a flame retardant filler. With this respect, electrical properties of the mineral reinforced polymeric composites were investigated in this study. After grinding of huntite/hydromagnesite mineral to the particle size of 10 μ m, 1 μ m, and 0.1 μ m, phase and microstructural analyses were undertaken using X-ray diffraction (XRD) and scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS). The ground minerals with different particle size and content levels were subsequently added to ethylene vinyl acetate copolymer (EVA) to produce composite materials. After fabrication of huntite/hydromagnesite reinforced plastic composite samples, they were characterized by using Fourier transform infrared (FTIR) and SEM-EDS. Electrical properties were measured as a main objective of this paper with Alpha-N high resolution dielectric analyzer as a function of particle size and loading level. Dielectric constant, dissipation factor, specific resistance, and conductivity of the composite materials were measured as a function of frequency. On the other hand, conductivity of Ag-coated and uncoated polymeric composite materials was measured. It was concluded that the electrical properties of plastic composites were improved with reducing the mineral particle size.